Overexpression of gene DEP domain containing 1 and its clinical prognostic significance in colorectal cancer. Issue 12 (3rd November 2020) - Shen, Xiaohan; Han, Jinming
Abstract: Background: Colorectal cancer (CRC) is one of the most commonly seen malignancies worldwide, yet its regulatory mechanisms still need to be further illuminated. Abundant evidence revealed that aberrant expression of cancer‐related genes contributes to CRC progression. DEP domain containing 1 (DEPDC1) has been found to play a crucial role in the carcinogenesis and development of malignancies. Nevertheless, limited studies have been concerned with the role of DEPDC1 in CRC. This study aimed to investigate the relationship between DEPDC1 expression and CRC clinicopathological parameters. Methods: Solid CRC tissues and adjacent noncancerous tissues (ANCTs) (n = 150) were chosen randomly to detect the mRNA expression levels of DEPDC1 by real‐time quantitative reverse transcription‐polymerase chain reaction (RT‐qPCR). Formalin‐fixed, paraffin‐embedded (FFPE) blocks of CRC tissues and ANCTs (n = 150) were acquired to examine DEPDC1 protein expression levels by immunohistochemistry (IHC). Results: DEPDC1 was significantly overexpressed in CRC tissues than that in ANCTs ( P < .05 ). High protein expression of DEPDC1 was associated with poorer TNM stage and recurrence ( P < .001 and P = .003, respectively). Kaplan‐Meier survival analysis showed significantly shorter overall survival (OS) and disease‐free survival (DFS) in DEPDC1 protein high‐expression group compared with low‐expression group ( P < .05). Univariate analysis demonstrated that DEPDC1 protein expression was correlated with DFS ( P = .005) and OS ( P = .006). Multivariate analysis revealed that the combination of DEPDC1 protein expression and TNM stage has statistical significance in CRC prognosis prediction ( P = .024 and P = .009, respectively). Conclusions: DEPDC1 may act as a potential biomarker for CRC detection as well as a prognostic predictor concerning the survival of CRC patients. Abstract : In total, 150 CRC patients were enrolled in the study. By IHC, we observed that the staining of DEPDC1 was in nucleus of CRC tumor cells. Representative immunostaining of DEPDC1 in CRC tissues and ANCTs (EnVision) are shown in Figures (A)‐(F): (A) CRC positive, weak (×100); (B) CRC positive, weak (×200); (C) CRC positive, strong (×100); (D) CRC positive, strong (×200); (E) ANCTs negative, (×100) (F) ANCTs negative, (×200). By RT‐qPCR, DEPDC1 was found significantly highly expressed in CRC tissues than in ANCTs (n = 150, * P < .05), shown in Figure (G). By Kaplan‐Meier analysis, DEPDC1 overexpression predicted poorer DFS and OS in CRC patients. (H) Relationship between DEPDC1 protein expression and DFS. (I) Relationship between DEPDC1protein expression and OS.